Successful outcome of pregnancy with chronic myeloid luekamia with preterm premature rupture of membranes - Kaundinya, Aditi Pradeep; Cardoso, Pia Muriel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The concomitant occurrence of pregnancy and chronic myeloid luekamia (CML) is uncommon and hence its management often poses a dilemma due to limited data available for the same. There is also very sparse data available with respect to the use of imatinib in pregnancy (which is usually the mainstay in the management of CML with few case reports suggesting congenital anomalies in the fetus. We presented a case report of a known case of CML who was in the chronic phase on tablet imatinib 300 mg OD. She presented with preterm premature rupture of membranes (PPROM) at 28 weeks and was given conservative management for the same, she went into preterm labour at 32 weeks and delivered vaginally a healthy 1.8 kg male baby without any intrapartum or postpartum complications. Both mother and baby were in good health at six month follow up. We had to weigh carefully the risks of immune-compromised state of the patient versus the complications of preterm delivery and tread through the management of this particular case. Use of imatinib did not cause any obvious congenital malformations in the baby.